Evaluation of Legal Protection for Women and Children’s Victims of Violence by the Bengkulu City Office of Women's Empowerment and Child Protection - Meilisa, Meilisa; Fitri, Sherly Nelsa (Universitas Muhammadiyah Yogyakarta, 2025)
The issue of violence against women and children represents a significant human rights violation that persists as a pervasive challenge in Bengkulu City. The objective of this research is to evaluate the implementation of legal protection for women and children’s victims of violence by the P3AP2KB Office of Bengkulu City. The research method employed is normative legal research, utilizing a combination of statutory, conceptual, and theoretical approaches. The findings indicate that the P3AP2KB Office has implemented a range of legal protection initiatives, encompassing both preventive and repressive measures. These have been achieved through the provision of legal, psychological, and medical services, as well as through the strengthening of public awareness through the Gelang Peti program. Nevertheless, several challenges persist, including social stigma, limited resources, and a lack of coordination between agencies. To ensure the sustainability of legal protection for victims of violence, it is essential to strengthen resources, enhance community education, and foster institutional synergy.